Compassion Fatigue in Clinical Nurses: An Evolutionary Concept Analysis - sabery, Mahdieh; Zagheri tafreshi, Mansoureh; Hosseini, Meimanat; Mohtashami, Jamileh; Ebadi, Abbas (Advances in Nursing & Midwifery, 2018)
Background: Despite the agreement regarding the significance of the concept of CF in nursing, it has been unrecognized, and there is no clear definition of compassion fatigue in the context of nursing Objectives: The aim of this study is to inductively develop or formulate a clear and uniformed definition of compassion fatigue in the context of nursing. Patients and Methods: A Concept analysis using Rodger’s approach using a literature-based method and thematic analysis was conducted. Steps of Rodger’s concept analysis encompass identify the concept and associated definition, attributes, antecedents, consequences, surrogate terms, related concepts, and a model case exemplar. Results: attributes, antecedents and consequences of compassion fatigue from literatures is extracted and then a <span style="line-height: 105%; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN;" lang="EN">vivid definition is achieved. Conclusions:<span style="font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-bidi-language: FA; mso-fareast-font-family: ’Times New Roman’;">this analysis demonstrated that the concept of compassion fatigue is comprised of excessive empathy, the symptomatology of secondary traumatic stress, the problematic work environment of burnout and coping mechanism deficit. Keywords: Compassion fatigue, Secondary traumatic stress, nurse, concept analysis